2022
DOI: 10.1200/edbk_351354
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in Colorectal Cancer: The Long and Winding Road From Negative Predictive Factor to Positive Actionable Target

Abstract: Human epidermal growth factor receptor 2 ( HER2) is a well-known oncogenic driver in different tumors and an approved therapeutic target in breast and gastroesophageal cancer. In metastatic colorectal cancer, only 3% to 5% of patients present with HER2 alterations: somatic mutations and amplifications. HER2 was first assessed as a biomarker of resistance to anti- EGFR therapy; however, in more recent years, its role as a potential actionable target has emerged. In this article, we discuss the predictive and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 86 publications
1
40
0
Order By: Relevance
“…Moreover, a potential use in assessing the dynamics of RAS to monitor response and resistance to treatment has been suggested ( Table 2 ) [ 71 ]. Another example is HER2 , a well-known oncogenic driver in different tumor types [ 76 ]. Although its alterations are not common in CRC (3–5% of mCRC cases), when present, anti-HER2 therapy is an option [ 15 ].…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…Moreover, a potential use in assessing the dynamics of RAS to monitor response and resistance to treatment has been suggested ( Table 2 ) [ 71 ]. Another example is HER2 , a well-known oncogenic driver in different tumor types [ 76 ]. Although its alterations are not common in CRC (3–5% of mCRC cases), when present, anti-HER2 therapy is an option [ 15 ].…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…HER2 was first established in gastric cancer in the ToGA trial in 2010, which overexpresses HER2 in up to 20% of cases as a clinically valuable target ( 56 ). In mCRC, alteration in HER2 accounts for only up to 5% of cases and appears to be enriched in RAS -WT CRC, accounting for up to 40% in cases showing resistance to EGFR base antibody therapies ( 57 , 58 ).…”
Section: Relevant Clinical Resistance Mechanismsmentioning
confidence: 99%
“…However, upfront testing of KRAS -WT CRC for HER2 amplification or mutation is currently not recommended in the ESMO or ASCO guidelines. Targeting HER2 in mCRC currently finds its place in second or later lines ( 58 , 61 ). First line trials are currently recruiting.…”
Section: Relevant Clinical Resistance Mechanismsmentioning
confidence: 99%
“… 101 Thus far, patients with mCRC harboring tumor HER2 mutations have not responded to single-agent HER2 small molecule inhibitors in clinical trials 134 ; however, this may be due to the varying sensitivities of different HER2 mutations to anti-HER2 monotherapy. 135 In addition, only clinical trials of anti-HER2 combination therapies, not monotherapy, have demonstrated efficacy in HER2-expressing mCRC. 136 Dual HER2-targeted therapy has demonstrated anti-tumor activity in preclinical studies using xenograft models of HER2 -mutated mCRC 137 and anti-HER2 combination regimens continue to be evaluated in clinical trials for HER2 -positive patients with mCRC (NCT05350917, NCT03457896, NCT04639219, and NCT04579380).…”
Section: Extended Biomarker Testing Optionsmentioning
confidence: 99%